Pulmonary function test in children: Multiple Breath Washout (MBW) – a position statement of the Polish Society of Pediatric Pulmonology (STAN PNEUMO: MBW) - Walicka-Serzysko, Katarzyna; Postek, Magdalena; Wasilewska, Eliza; Peradzyńska, Joanna; Krenke, Katarzyna; Doniec, Zbigniew; Wojsyk-Banaszak, Irena (Family Medicine & Primary Care Review, 2025)
The multiple breath washout (MBW) test is a highly sensitive method for detecting early abnormalities in pulmonary function through the assessment of ventilation distribution. As it does not rely on forced respiratory maneuvers, MBW can be successfully performed in young children and individuals with limited ability to cooperate. This technique is particularly valuable in identifying both early, reversible changes caused by localized inflammation and mucus retention, as well as irreversible structural damage resulting from fibrosis and progressive destruction of the lung parenchyma in peripheral airway diseases. The growing availability of commercial MBW devices has facilitated its adoption in clinical research and contributed to its increasing integration into routine clinical practice. This position statement by the Polish Society of Pediatric Pulmonology outlines the technical aspects of the MBW procedure, guidance for interpreting test results, and potential clinical applications.